Little woodchucks : Offerman woodshop's guide to tools and tomfoolery - Offerman, Nick, 1970-; Buchanan, Lee, 1977 (Dutton, 2025)
"In his long running hit book Good Clean Fun, Nick Offerman brought us into his woodshop with personal reflections on woodworking alongside instructions to create some of his favorite projects. Now, in Little Woodchucks, the Offerman Woodshop is opening its avuncular doors to woodworkers of all ages in the form of twelve brand-new, family-friendly projects perfect for kids, from beginner projects like a handmade box kite to more challenging offerings like a little free library/meat locker. Combining his signature wry humor with clearly written and joyfully illustrated project instructions, Little Woodchucks is the perfect way to encourage eye contact and other old-fashioned familial engagements, while introducing young woodworkers-to-be to the satisfaction and good, clean fun of hands-on crafting."-- Provided by publisher.